Penerapan Standar Operasional Prosedur Terhadap Efektifitas Pelayanan Keuangan di IAIN Sultan Amai Gorontalo: - - Sulam, Sulam; Domopolii, Mujahid; Usman Dilo, Asna (Al-Buhuts, 2019)
Standard Operating Procedure (SOP) is an instrument that contains the processes and procedures of an activity based on a standard that has been standardized. This study determined the effect of the application of standard operating procedures on the effectiveness of financial services, especially at IAIN Sultan Amai Gorontalo. This research used a quantitative approach, with data collection methods through tests, questionnaires, and interviews. Data analysis was conducted to test the effect of the tested variables, namely the application of SOP (X) to IAIN Sultan Amai Gorontalo financial services (Y). The results showed that the application of SOP conducted at IAIN Sultan Amai Gorontalo influenced financial services at IAIN Sultan Amai Gorontalo. In its implementation, the SOP implemented at IAIN Sultan Amai Gorontalo has made financial services easier and more directed.